2002
DOI: 10.1128/aem.68.6.3055-3066.2002
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Profiling of a Complex Microbial Community by High-Throughput Sequencing

Abstract: Complex microbial communities remain poorly characterized despite their ubiquity and importance to human and animal health, agriculture, and industry. Attempts to describe microbial communities by either traditional microbiological methods or molecular methods have been limited in both scale and precision. The availability of genomics technologies offers an unprecedented opportunity to conduct more comprehensive characterizations of microbial communities. Here we describe the application of an established mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 53 publications
2
83
0
Order By: Relevance
“…Phylogenetic representation in the distal SI also increases and includes those genera indicated previously, plus members of genera within the Clostridiales and Bacteriodetes families (Hill et al, 2004;Richards et al, 2005). Complexity of the microbial community is greatest in the large intestine, where the density increases to 10 10 to 10 12 CFU per gram and the community is dominated by gram-positive genera, including Clostridium, Bacillus, Ruminococcus, and Fusobacterium (Hill et al, 2002;Leser et al, 2002). Variation within bacterial species among locations in the GI tract 12 also substantially contributes to overall gut microbial diversity and function (Dixit et al, 2004).…”
Section: Localization Of Gut Microbiotamentioning
confidence: 92%
“…Phylogenetic representation in the distal SI also increases and includes those genera indicated previously, plus members of genera within the Clostridiales and Bacteriodetes families (Hill et al, 2004;Richards et al, 2005). Complexity of the microbial community is greatest in the large intestine, where the density increases to 10 10 to 10 12 CFU per gram and the community is dominated by gram-positive genera, including Clostridium, Bacillus, Ruminococcus, and Fusobacterium (Hill et al, 2002;Leser et al, 2002). Variation within bacterial species among locations in the GI tract 12 also substantially contributes to overall gut microbial diversity and function (Dixit et al, 2004).…”
Section: Localization Of Gut Microbiotamentioning
confidence: 92%
“…Others have reported that early and key steps in the ribosomal approach such as those pertaining to PCR conditions and template to product ratios affect the composition of the resultant clone libraries (Mathieu-Daudé et al, 1996;Suzuki and Giovannoni, 1996;Polz and Cavanaugh, 1998;Bonnet et al, 2002;Hongoh et al, 2003). In addition, high DNA sequencing costs until recently meant analysis of small sequences and small, unrepresentative libraries was tacitly accepted (Hill et al, 2002). It remains to be seen if high-throughput cultivation and sequencing techniques will enable 'molecular methods' to fulfill the promise of detecting all microbes in a community, or if we really never will know the true extent of microbial diversity (Curtis et al, 2002).…”
mentioning
confidence: 99%
“…Briefly, after overnight culture from frozen stocks in TS broth, bacterial cells were harvested by centrifugation and genomic DNA was extracted with phenol-chloroform-isoamyl alcohol according to previously described methods (Dumonceaux et al, 2006). The cpn60 UT was amplified by PCR using 1 ml of extracted DNA, 0.5 U of Taq polymerase, 50 mM MgCl 2 , 10 mM of dNTPs (deoxynucleotide triphosphates) and 0.375 mM for each of the degenerate primers H729 and H730 (Hill et al, 2002). Reactions were subject to 958C for 3 min, followed by 40 cycles of 1 min at 958C, 1 min at 468C, 1 min at 728C and a terminal 5 min extension at 728C.…”
Section: Source and Synthesis Of Radiotracersmentioning
confidence: 99%